Parentalidade em casais homossexuais - Araldi, Marina Ortolan (Universidade do Vale do Rio dos Sinos, 2015)
This research is based on the perception that families formed by same-sex couples are increasingly more common in modern society, but still a less studied minority. This is a master degree dissertation that is organized in two papers. The first paper is a systematic review of the literature on same-sex parenting. The second paper is a qualitative study that aimed to investigate the process and the parenting of four same-sex couples. The results of both papers suggest that parental role are not rigid, and favor affection, respect and acceptance of differences in parent-child relationship and in childcare. Parenthood reveals maturity as a couple and implies coping with prejudices that are more easily overcome with social and family support.
Keywords: Parentalidade; Homoparentalidade; Casais do mesmo sexo; Homossexual; Família; Parenthood; Same-sex parent; Homosexual; Family; ACCNPQ::Ciências Humanas::Psicologia